2019
DOI: 10.1111/jce.14250
|View full text |Cite
|
Sign up to set email alerts
|

SVT discrimination algorithms significantly reduce the rate of inappropriate therapy in the setting of modern‐day delayed high‐rate detection programming

Abstract: Background Contemporary implantable cardioverter‐defibrillator (ICD) programming involving delayed high‐rate detection and use of supraventricular tachycardia (SVT) discriminators has significantly reduced the rate of inappropriate shocks. The extent to which SVT algorithms alone reduce inappropriate therapies is poorly understood. Methods and Results PainFree SST enrolled 2770 patients with a single‐ or dual‐chamber ICD or cardiac resynchronization defibrillator. Patients were followed for 22 ± 9 months with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Regarding inappropriate ICD shocks, the prevalence reported in major trials (60)(61)(62)(63) ranges between 11% and 32%, although this is largely outdated in newer studies applying upto-date programming and arrhythmia discriminators, showing a two-years inappropriate shock rate of 3% (64,65). Inappropriate ICD therapies may have a proarrhythmic effect (66, 67), but the associated incidence of syncope is little unknown yet.…”
Section: And Table 2)mentioning
confidence: 99%
“…Regarding inappropriate ICD shocks, the prevalence reported in major trials (60)(61)(62)(63) ranges between 11% and 32%, although this is largely outdated in newer studies applying upto-date programming and arrhythmia discriminators, showing a two-years inappropriate shock rate of 3% (64,65). Inappropriate ICD therapies may have a proarrhythmic effect (66, 67), but the associated incidence of syncope is little unknown yet.…”
Section: And Table 2)mentioning
confidence: 99%
“…Implantable cardioverter-defibrillators (ICDs) reduce mortality in patients at high risk of ventricular arrhythmias [1][2][3] . Previous ICD programming trials, such as Primary Prevention Parameters Evaluation (PREPARE), Multicenter Automatic Defibrillator Implantation Trial-Reduce Inappropriate Therapy (MADIT-RIT) and Avoid DeliVering TherApies for Non-sustained Arrhythmias in ICD PatiEnts III (ADVANCE-III), demonstrated that shock reduction strategies not only reduce shock rates but can also reduce hospitalizations and mortality over a follow-up period of up to 14 months [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] With contemporary programming of ICDs with delayed high-rate detection and the use of SVT discriminators, the rates of inappropriate shock and therapy can be reduced to around 3–4%. [ 7 ]…”
mentioning
confidence: 99%